2010
DOI: 10.1143/apex.3.092101
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Lift-Off Process for Blue Light-Emitting Diodes

Abstract: An epitaxial layer of an InGaN light-emitting diode (LED) structure was separated from a truncated-triangle-striped patterned-sapphire substrate through a chemical lift-off (CLO) process. A crystallographic stable and terminated V-shaped GaN grooved pattern was observed on the lift-off GaN surface. A peak wavelength blueshift phenomenon of the micro-photoluminescence spectrum was observed on the lift-off LED epitaxial layer (440.7 nm) compared with the LED/sapphire structure (445.8 nm). The free-standing LED e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…We can also observe in Fig. 5 that the sidewall of the a-plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) should only be formed by etching the inclined plane of the a-plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) first.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…We can also observe in Fig. 5 that the sidewall of the a-plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) should only be formed by etching the inclined plane of the a-plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) first.…”
Section: Resultsmentioning
confidence: 77%
“…Overall, we propose a complete and reasonable mechanism for the etching behavior of the whole KOH etching on GaN, and the experimental result is consistent with our theory. 5 The diagram of the shrinkage motion for (10-1-1) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) The study of wet etching on GaN surface by potassium……”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While several research groups have reported that CrN [5,6] and ZnO [7,8] can be used as not only buffer layers for GaN epitaxial growth but also sacrificial layers, that can later be laterally etched by the CLO process. Moreover, AlN thin film was also applied for sacrificial layer to fabricate InGaNbased LEDs on triangle-shaped and truncated-triangle-striped patterned sapphire [9,10]. Except the materials mentioned above, Ga 2 O 3 can also be selectively etched by a hydrofluoric (HF) solution to remove epilayers from sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The doping selective etching process on heavy doped GaN:Si layers had been reported for the chemical lift-off process in InGaN LED structures. 13,14,15,16 Most of the embedded air-gap structures in the InGaN LEDs were fabricated through the epitaxial re-growth process.…”
mentioning
confidence: 99%